Biometrical and histomorphometrical changes of testis in the dynamics of postnatal ontogenesis from birth to puberty of Black Bengal goat - Gofur, Md Royhan; Sadi, Md Sheikh; Aktar, Shabnaz; Khatun, Afia; Awal, Md Abdul; Alam, Md Emtiaj; Rauf, Shah Md Abdur; Matsuo, Koiochi (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: The study aimed to account for baseline biometrical and histomorphometric testicular changes in Black Bengal goats during postnatal development. Materials and Methods: Black Bengal goats, divided into group I of VII; day 0; 1, 2 weeks; 1, 2, 4, and 6 months of age, respectively, were used in this study. Results: The biometrical and histomorphometric values of the testis varied significantly (p < 0.05) from postnatal 1–2 months. From day 0 to 2 months, seminiferous tubules, called sex cords, contained simply peripherally placed Sertoli cells and centrally placed gonocytes. Gonocytes, positioned in the center, moved centrifugally in the direction of the basement membrane of sex cords with the advancement of age, transformed into prespermatogonia, and were distributed among the Sertoli cells at the edge of sex cords that make up the basal cell layer in nearly all of the seminiferous tubules by 2 months after birth. Initiation of spermatogenesis, i.e., stratification and lumination of seminiferous epithelium, took place in the 4th months. At 6 months, all types of spermatogenic cells had been identified. The onset of puberty, i.e., the establishment of spermatogenesis, was noticed to have been established at 6 months of postnatal age in Black Bengal goats, as shown by the spermatozoa that were adhered to the ad luminal border of the Sertoli cells and also in the tubular lumen. Conclusion: This research is the first to document the varying biometrical and histomorphometric measurements of the testis in Black Bengal goats from birth to puberty. J. Adv. Vet. Anim. Res., 10(2): 237–243, June 2023 http://doi.org/10.5455/javar.2023.j674